Trabectedin may be a valuable treatment option for elderly patients with metastatic soft tissue sarcomas - Miolo, Gianmaria; Buonadonna, Angela; Lombardi, Davide; Scalone, Simona; Lauretta, Andrea; Della Puppa, Lara; Corona, Giuseppe (Frontiers in Oncology, 2024)
Background In the landscape of metastatic soft tissue sarcoma (mSTS) treatment, anthracyclines have shown efficacy; however, their associated toxicity imposes significant limitations, especially in frail elderly patients with mSTS who are highly susceptible to severe adverse effects. In this context, trabectedin, due to its distinct pharmacological profile and safety profile, may represent an interesting alternative being demonstrated to be active in treating mSTS. These features hold particular significance for elderly and unfit patients with mSTS, where balancing treatment benefits with potential adverse effects represents the pivotal objective. Methods The investigation was focused on a specific group of 11 elderly patients with mSTS aged ≥70, all undergoing first-line treatment with trabectedin, and it was supported by comprehensive pharmacokinetic and pharmacodynamic studies. Among these patients, 9 out of 11 started the treatment at a dose of 1.5 mg/m2. Results The primary objective of this investigation is to highlight trabectedin as a valuable first-line treatment option for elderly and unfit patients with mSTS. Additionally, this investigation seeks to explore whether higher administered doses of trabectedin can enhance clinical outcomes while maintaining the same toxicity profiles. The median progression-free survival (PFS) was 77 days (95% CI, 53–89), the median overall survival (OS) was 397 days (95% CI, 66–2,102), while the overall toxicity of grade 3–4 severity amounted to 43%. Conclusion These findings provide new insights into the clinical outcomes and toxicity associated with trabectedin in an elderly patient population, enhancing our understanding of better treatment approaches for a specific population of patients with mSTS.